Technical and Economic Efficiency of Production Factors in Javanese Tobacco Farming: A Case Study of Belun Village, East Java - Alief Ramadhani Novita Cahyono Putri; Sri Widayanti; Gyska Indah Harya (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
This study analyzes the technical and economic efficiency of production factors in tobacco farming in Belun Village, Temayang Subdistrict, Bojonegoro District, East Java. Using stochastic frontier software 4.1, the analysis was conducted with a sample of 87 Javanese tobacco farmers. The production inputs evaluated include land area, seeds, urea fertilizer, NPK fertilizer, NPK Phonska Plus fertilizer, labor, pesticides, and production output. The results indicate that the gamma elasticity coefficient for technical efficiency is 0.949, with all variables being statistically significant at the 1% level (t-table 2.64), except for pesticide input, which is significant at the 5% level (t-table 1.99). In the economic efficiency analysis, seedlings were identified as the inefficient input with an efficiency estimate (EE) of > 1 (52.4), while other inputs showed EE < 1. The study concludes that 94.9% of the inefficiency stems from production factors, while 5.1% is attributed to external factors. Moreover, the inputs used in Javanese tobacco farming are neither technically nor economically efficient. To achieve full technical efficiency, farmers should reduce inputs such as land area, NPK fertilizer, and NPK Phonska Plus fertilizer, while increasing the use of seeds, pesticides, urea fertilizer, and labor.